Physical Quality and Organoleptic Quality of Mutton Meatballs with The Addition of Cassava Flour at Different Levels: Kualitas Fisik Dan Mutu Organoleptik Bakso Daging Kambing Dengan Penambahan Tepung Singkong Pada Level Yang Berbeda - Amalyadi, Rezki; Karni, Ine; Gifari, Zaid Al; Septian, I Gede Nano; Aminurrahman, Aminurrahman (BPFP Universitas Bengkulu, 2025)
This study aims to determine the effect of the addition of cassava flour in various levels on the physical and organoleptic quality of meatballs made from mutton. The physical and organoleptic quality tests included measurements of pH, cooking shrinkage, yield, aroma, taste, colour, and texture. The research design applied was a completely randomized design (CRD) with four treatments and five repetitions. For data analysis, ANOVA was used on physical parameters and organoleptic test with Kruskal Wallis method. The findings of the study showed that the highest pH, cooking shrinkage, and yield were achieved in P3, which was with the addition of cassava flour at the level of 20%. Aroma, flavour, and texture did not show a significant effect on the variation of the level of cassava flour addition. However, colour has a significant effect related to the level of cassava flour addition of 20%. It can be concluded that the addition of cassava flour at the level of 20% can affect the colour, pH, cooking shrinkage and yield of mutton meatballs.